Implementasi Numerasi pada Sekolah Penggerak di Sekolah Dasar - Nanda, Violyta Putri; Hariandi, Ahmad; Sholeh, Muhammad (Universitas Batanghari Jambi, 2024)
This research aims to describe the implementation of numeracy in driving schools in elementary schools. This research was carried out at State Elementary School 198/I Pasar Baru in the odd semester of the 2023/2024 academic year. Research data was obtained through observation, interviews and document study. The research subjects in this study were school principals, teachers and students. Test the validity of the data using triangulation. The results of this research show that the strategies used by teachers in improving numeracy skills in class V of State Elementary School 198/I Pasar Baru are consistent with literature which emphasizes the importance of strategies in achieving numeracy learning objectives.